Transfer of humoral and cell-mediated immunity via colostrum in pigs - Nechvatalova, Katerina; Kudlackova, Hana; Leva, Lenka; Babickova, Karolina; Faldyna, Martin (Veterinary immunology and immunopathology, 2011)
The first aim of our study was to obtain information on the transmission of antigen-specific antibodies from colostrum to respiratory tract mucosa in piglets. The second aim was to confirm the biological relevance of the presence of lymphocytes in colostrum and the already described fact that these cells can penetrate the intestinal barrier and "colonize" peripheral blood and lymphatic tissues of piglets. Therefore, we performed an experiment in which sows were immunized with a model antigen Keyhole Limpet Hemocyanin and their piglets were euthanized at different intervals after birth and colostrum intake. Colostrum, bronchoalveolar lavage fluid and blood samples were collected for serological detection of antigen-specific antibodies. Lymphocytes isolated from peripheral blood and lymphatic tissues (mesenteric and tracheobronchial lymph nodes and spleen) of piglets were in vitro activated with the antigen. We found that colostrum-derived antibodies can cross into the respiratory tract mucosa. Furthermore, we found that antigen-specific lymphocytes were detectable in mesenteric lymph nodes and peripheral blood, but very rarely in spleen and tracheobronchial lymph nodes.
Keywords: Lymphoid Tissue; buněčná imunita; lymfoidní tkáň; Animals, Newborn; Colostrum; Immunity, Cellular; novorozená zvířata; Immunity, Maternally-Acquired; Swine; aktivace lymfocytů; Respiratory Mucosa; ženské pohlaví; zvířata; Lymphocyte Activation; humorální imunita; imunita získaná od matky; Immunity, Humoral; respirační sliznice; prasata; kolostrum; Female; Animals